Jamaah Pengajian Sebagai Institusi Pendidikan Tertua (Refleksi Tujuan, Historis Dan Eksistensinya) - Nanang Abdillah (Program Studi Pendidikan Agama Islam, 2021)
The recitation congregation is a community or group of seekers of religious knowledge by means and methods of recitation that use the wetonan system, namely the congregations come in flocks on certain time. As for their goal, the recitation congregations are the formation of personality in themselves and their families so that they become Muslims who master Islamic teachings and practice them, so that they are beneficial to religion, society and the state. The emergence of the recitation congregation was the creative hand of Sheikh Maulana Malik Ibrahim as the first propagator of Islam in Java. This also shows that the recitation congregation is an educational model that is as old as the entry of Islam in Indonesia. The life of the recitation congregation has gone through a tortuous experience. Various major challenges have been faced through strategic steps so that they are able to survive until now and are recognized as assets as well as development potential. The resilience of the recitation congregation is due to the unique pattern of life, the institutionalization of the recitation congregation in society, the Javanese culture which is able to absorb foreign culture through a process of interiorization without losing its identity. The resilience of this recitation congregation becomes more attractive when compared to similar educational institutions in other countries.